(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The work studied the effectoffine silicon carbide (SiC) powder with (0,3,5,7)wt % on the thermal conductivity and mechanical properties of unsaturated polyester composite in the presence of a fixed amount of chopped glass fiber. The hand lay-up technique was employed to preparethe required samples. Results showed that tensile, impact strength and thermal conductivity increased with increasing the weight fraction of reinforced materials.